Accident Damage Analysis Module (ADAM): Novel European Commission tool for consequence assessment—Scientific evaluation of performance - Fabbri, Luciano; Wood, Maureen Heraty (Process safety and environmental protection, 2019)
This paper summarises the scientific evaluation of the performance of a novel modelling tool, the Accident Damage Assessment Module (ADAM), developed by the Joint Research Centre (JRC) of the European Commission (EC) to assess the consequences of an industrial accident resulting from an unintended release of a dangerous substance. The ADAM tool is specifically intended to assist Competent Authorities in the European Union (EU) and European Economic Area (EEA), and their supporting research institutions, responsible for the implementation of the Seveso Directive in their countries, as well as governmental and research organisations of EU Accession and Candidate Countries, and European Neighbourhood Policy countries involved in chemical accident prevention and preparedness. In particular, the tool provides decision-making support to various functions associated with industrial risk management, enforcement and oversight, including risk analysis, land-use and emergency planning, inspection and monitoring, and the preparation and review of safety reports. Consequence assessment models are characterised by high level of complexity and of uncertainty. It is therefore of paramount importance to assess their limits. The scientific evaluation was conducted across the entire consequence assessment cycle, including the source terms and the physical effects calculations associated with the concentration toxics after airborne dispersion, the thermal radiation of chemical fires, and the explosion of vapour flammable clouds. The evaluation described in this paper was conducted on a series of relevant scenarios, by benchmarking the outcome of ADAM with the results obtained by similar software tools and with the experimental data obtained on a series of reference field campaigns, as taken from the literature.